Customer's perception towards McDonald's icon-based nutritional labels - Samsudin, Azlina; Jusoff, Kamaruzaman; Md. Zaini, Zetty Madina; Musa, Mushaireen; Khalid, Khazainah; Ngali, Norzaidah; Rahmat, Norazlina; Ramli, Noorazlin; Abd Ghani, Fatimah; Hamid, Munirah (IDOSI Publications, 2011)
Nowadays, nutritional labels are very important instruments in the restaurant industry as it helps customers in making informed food choices. Therefore, McDonald’s should take action to become the first in the world to make extensive nutritional information and comprehensive ingredient listings and other food facts available to the customers. Additionally, McDonald’s provided in-store nutrition information pamphlets, on food wrappers, on tray placemats as well as official restaurant website in order to let the customers be aware of it. However, McDonald’s are always perceived as unhealthy restaurants and portray a bad image to the public. In relation to that, in order to change public perception towards fast foods, nutrition label acts as a safety guide in choosing healthy foods. Thus, this study aims to determine customers’ perception on the icon-based nutrition labels of McDonald’s food products. The study was conducted at McDonald’s outlets within Shah Alam area and the data was gathered through self-administered questionnaires. From the analyses, the results showed that customers positively perceived McDonald’s icon-based nutrition labels as a good effort and step towards healthier lifestyle as people nowadays are more conscious and aware of their health and nutritious food intake. Furthermore, the findings revealed some important points which could be useful for the fast food operators, food manufacturers as well as other restaurant operators to come out with the idea of producing nutrition labels as a new marketing strategy or tool. Additionally, it will increase customer turn over, as well as create a new environment geared towards a healthy lifestyle. As a final point, for future researchers they should explore on the effectiveness of nutritional labels on the customer in terms of making healthy food choices. In addition, the study can be broadened to investigate whether nutritional labels help build more trust in providing nutrition information to the customers in making decisions to buy a meal.